1995
DOI: 10.1177/096032719501401203
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal iron and cobalt absorption and iron status in young rats and guinea pigs

Abstract: The gastrointestinal absorption of Fe and Co by rats and guinea pigs of different ages was measured by comparing the whole-body retention of 59Fe and 57Co after oral and intraperitoneal administrations. The age-groups studied included newborn, weanlings and adults. The absorption of both Fe and Co decreased markedly with age in both rats and guinea pigs. In the rat, absorption remained ele vated during the suckling period, while in the guinea pig absorption decreased markedly duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Nevertheless, it should be recognized that age-dependent pharmacokinetic factors other than metabolism may also affect the bioavailability of DLM and the magnitude of its adverse effects. Preweanling rats are shown to have relatively high GI absorption rates (Hoffman, 1982;Naylor and Harrison, 1995). Pglycoprotein, which may play a role as an efflux transporter of pyrethroids (Bain and LeBlanc, 1996;Buss et al, 2002) has been found to be deficient in young mice (Mahmood et al, 2001).…”
Section: Age-dependent Toxic Signs Following Dlm Administrationmentioning
confidence: 99%
“…Nevertheless, it should be recognized that age-dependent pharmacokinetic factors other than metabolism may also affect the bioavailability of DLM and the magnitude of its adverse effects. Preweanling rats are shown to have relatively high GI absorption rates (Hoffman, 1982;Naylor and Harrison, 1995). Pglycoprotein, which may play a role as an efflux transporter of pyrethroids (Bain and LeBlanc, 1996;Buss et al, 2002) has been found to be deficient in young mice (Mahmood et al, 2001).…”
Section: Age-dependent Toxic Signs Following Dlm Administrationmentioning
confidence: 99%
“…This variable, estimated by taking into account the contribution of both villi and microvilli, increases by up to 20-fold in the jejunum during the main stages of chicken development. In the guinea pig, nutrient transporters are expressed in the second half of gestation (Buddington and Diamond, 1989), their uptake peaks at birth, declines until weaning and remains almost unchanged thereafter (Juan et al, 1998;Naylor and Harrison, 1995;Heubi and Fondacaro, 1982;Himukai et al, 1980). In the present work, the same morphometric strategy was adapted to the guinea pig small intestine to estimate the changes in mucosal surface area that may accompany the maturation process of intestinal absorptive function.…”
Section: Introductionmentioning
confidence: 98%
“…1996 ), although the ratio between these two pathways has not been determined in mammals. Net absorption of K + and other ions in the colon of young rats is significantly higher than in adult rats ( Naylor & Harrison 1995, Aizman et al . 1996 ).…”
Section: Discussionmentioning
confidence: 99%